P135 Lung function in post-transplant multiple myeloma patients. (16th November 2010) - McConkey, H; Streetly, M; Sachchithanantham, S; Gillion, M; Kazmi, M; Raj, K; Milburn, H J
Abstract : Introduction: Chemotherapy followed by autologous stem cell transplant (SCT) is the standard of care for patients with multiple myeloma. However, both conditioning and transplantation increase patient susceptibility to pulmonary complications, a major cause of morbidity and mortality. Pulmonary function tests (PFTs) are routinely performed before and after SCT, providing a means to detect any early decline in pulmonary performance. We report a retrospective analysis of patients undergoing treatment for myeloma at a tertiary London hospital with pre-and post SCT PFTs to assess the impact of transplantation on pulmonary function. Methods: Patients were assessed with serial PFTs pre and post SCT (initially 6 weeks and thereafter 3 monthly). Standardised PFTs were expressed as a percentage of the pre-transplant value (100%). Tests were carried out by the same personnel, to ensure standardisation and eliminate variability in patient performance. Results: 34 patients with myeloma with median age at SCT of 50 years (range 36–69) were analysed. Conditioning therapy utilised high dose melphalan in 14 and TBI in 18. Median follow-up was 12 months (range 1.5–102) and a median of 4.5 PFTs was performed (range 2–21). FEV1 was reduced by >10% in 14/34 and five of these had >20%. FVC decreased >10% in 7/34 and >20% in 6/34. TLCO was reduced by >10% in 23/34 and >20% in 12/34 patients. KCO decreased in 25/34 (>10%) and 12/34 (>20%) patients. The median time for maximum reduction was between 2.25 and 4 months for all tests. An improvement in PFT to >90% baseline occurred in over 50% of patients who had repeat investigations and this occurred within 24 months of initial PFT reduction. No significant difference was observed between TBI and melphalan based conditioning approaches. Conclusion: Reductions in FEV1 or FVC were observed in a minority of patients whereas a majority had a reduction in TLCO/KCO—a significant proportion experiencing >20% fall. This reduction occurred early post transplant and improved for many. These changes may reflect possible pulmonary toxicity associated with conditioning therapy, post transplant lung injury or a combination of both and illustrates the necessity for regular prospective monitoring of PFTs following SCT for myeloma.